2017
DOI: 10.1017/s0272263117000080
|View full text |Cite
|
Sign up to set email alerts
|

TBLT and L2 Pronunciation

Abstract: Decades of research on task-based language teaching and learning (TBLT) have demonstrated that tasks may encourage second/foreign language (L2) development by providing conditions for cognitive processes and social interactions that facilitate L2 acquisition (e.g., Long, 2015; Robinson, 2011; Skehan, 2014; for alternative, noncognitive viewpoints on TBLT, see Jackson & Burch, 2017). Specifically, manipulating task features has been shown to draw learners' attention to target forms within meaningbased interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 70 publications
1
6
0
1
Order By: Relevance
“…Overall, respondents' generally positive views of communicative activities are consistent with state-of-the-art pedagogical recommendations and research (e.g. Gurzynski-Weiss et al, 2017;Saito, 2015).…”
Section: Differences and Difficultiessupporting
confidence: 72%
See 1 more Smart Citation
“…Overall, respondents' generally positive views of communicative activities are consistent with state-of-the-art pedagogical recommendations and research (e.g. Gurzynski-Weiss et al, 2017;Saito, 2015).…”
Section: Differences and Difficultiessupporting
confidence: 72%
“…In addition to recent studies that have set PI into a communicative framework, balancing meaning-oriented learning objectives with form-focused instruction, researchers have begun to incorporate the principles of task-based language teaching into PI (Gurzynski-Weiss et al, 2017). For instance, in a study manipulating the complexity of an information-gap task targeting Spanish vowels, Solon, Long, and Gurzynski-Weiss (2017) found that learners in simple and complex conditions produced a similar number of language-related episodes that were pronunciation-focused, but the production of /e/ became more targetlike only for learners who completed the more complex task.…”
Section: Literature Review 1 the Effectiveness Of Various Approaches ...mentioning
confidence: 99%
“…La recherche portant sur la prononciation et l'ELBT est émergente. Elle confirme que cette compétence spécifique qu'est la prononciation peut aussi être ciblée à travers cette approche pédagogique (Gurzynski-Weiss, Long et Solon, 2017).…”
Section: Discussionunclassified
“…TBPT makes use of the task-design principles of TBLT to enhance learners' attention to phonetic form in pedagogic tasks that involve meaning-based interaction. TBLT adopts meaning-based communicative tasks as central to defining language learning needs, goals, classroom activities, and assessment, but has not devoted research efforts to investigating pronunciation-focused communicative tasks until recently [89]. Based on [90]'s Framework for Task-Based Learning, a commonly used TBPT task-design implementation procedure [12][13][14] involves three stages, namely, pre-task, task cycle, and post-task.…”
Section: Task-based Pronunciation Teaching (Tbpt)mentioning
confidence: 99%
“…For example, according to the Cognition Hypothesis [91], making a communicative task cognitively more complex by increasing the number of elements and reasoning demands needed to complete the task leads to the production of more lexically and grammatically complex language, thus implicitly enhancing L2 development. Recent research [89] indicates that manipulating task-design variables is effective at enhancing learners' attention to phonetic form in meaning-based tasks, resulting in improvements in the perception and production of L2 segmental [12,13,15] as well as suprasegmental features of L2 speech [92], and speech comprehensibility [10]. As learners tend to engage in such interactive tasks collaboratively, task performance often leads to the occurrence of pronunciation-focused language-related episodes (P-LRE) [93] that serve to raise learners' awareness of pronunciation issues and indicate the extent to which the task design was effective at helping learners focus on pronunciation.…”
Section: Task-based Pronunciation Teaching (Tbpt)mentioning
confidence: 99%